Using photographs in consumer research of agricultural and livestock products - Manfroi, Julia Vettori; Franco, Mariane Ferreira; Garcia, Pedro Henrique de Melo; Pinheiro, Rafael Silvio Bonilha (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Photographs provide momentary visual data that facilitate consumer understanding, thus visual research methods have been used to obtain their perceptions and experiences. We aimed to conduct a literature review using studies related to the theme of this paper, to obtain an overview of sustainability, animal welfare, consumer behaviour, and the use of photographs in animal science research. The analysis method considered was qualitative and the information was obtained from scientific articles from Google Scholar, Scientific Electronic Library Online (SciELO) and Elsevier research platform databases, published in the last seven years, as well as from classical bibliographies to carry out a bibliographic survey related to the theme of the study. It was concluded that during the meat buying process, consumers' choices are determined mainly by the lowest price, origin, brand, product information, color, marbling, amount of fat, texture, freshness, type of cut and product conservation. The consumption of products from sustainable production and with animal welfare is still very low, mainly due to socioeconomic issues and lack of knowledge about the production process of animal products. The adoption of photographs in consumer research is capable of increasing the information load with reduced cognitive effort, reducing uncertainties during decision making. There is still a scarcity of works with photographs related to animal science and the increase would be opportune to avoid possible misinterpretations by consumers during the survey questionnaires.